All Hell Can't Stop Us: The On-to-Ottawa Trek and Regina Riot - Waiser, W. A. (Bill) (Fifth House Books, 2003)
In early June 1935, one thousand relief-camp strikers clambered aboard freight trains to take their grievances to Ottawa. Their trek would end in bloodshed on the streets of Regina on 1 July 1935, later known as "The bloodiest day of the Depression." In All Hell Can't Stop Us, noted historian Bill Waiser examines the social and political background of the On-to-Ottawa Trek and Regina Riot, and provides an in-depth account of the strikers, their supporters, and their powerful adversaries. This gripping history includes many unpublished sketches and photographs. --Publisher's description
Keywords: Unemployed -- Canada -- History -- 20th century